Efficiency of township hospitals in China in the context of the drug policy reform: Progress should not get bogged in midstream - A case study from a survey in Weifang prefecture - Laurène Petitfour; Xiezhe Huangfu; Martine Audibert; Jacky Mathonnat (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
Since the early 2000s, China has embarked on a major reform program in the field of health. Three are essential and linked: rebuilding a new health insurance system in rural areas, restructuring the organization and management of hospitals, halting the sharp rise in drug prices. To cope with the rising price of drugs, in 2009 the Chinese government launched a large pharmaceutical reform. Its key element is the implementation of a National Essential Medicine List (NEML), leading to a reorientation of incentives for health services financing. Health facilities are no longer allowed to make any profit on drug sales ("zero mark-up policy"), while this used to be their main source of revenue. Authorities have implemented different compensation schemes. In the context of redesigning the financing structure of health care facilities, it is crucial to understand how the NEML reform has affected—or not—the activity and efficiency of health care facilities, since the search for greater efficiency in the health system is a transversal and underlying objective of the three reforms mentioned above.This study relies on survey data from a sample of 30 randomly selected Township Hospitals (TH) in rural area from the prefecture of Weifang, in the Shandong province. Using a two-stage procedure, the study aims at assessing the technical efficiency scores of Township Hospitals and then at identifying the determinants of this efficiency. The first stage is realized with a non-parametric frontier approach, "partial frontier" method (order-m), to deal with the problem of dimensionality of the sample. The identification of the determinants of efficiency is made with fractional regressions (Ramalho, 2011). Results show that the average efficiency remains constant from 2006 to 2009 and 2010 to 2012, at around 0.65. The most significant and robust factors of technical efficiency are the share of subsidies in the TH incomes (negative effect) and the number of covered inhabitants per bed (positive effect). The study suggests that even after the implementation of the drug reform, a "soft budget constraint" effect remains, as well as financial barriers to universal access to healthcare (importance of demand-side determinants) and a phenomenon of oversizing of some THs.
Keywords: 330